Is the use of modafinil, a pharmacological cognitive enhancer, cheating?. Issue 2 (4th May 2018) - Porsdam Mann, Sebastian; de Lora Deltoro, Pablo; Cochrane, Thomas; Mitchell, Christine
Abstract: Drugs used to provide improvement of cognitive functioning have been shown to be effective in healthy individuals. It is sometimes assumed that the use of these drugs constitutes cheating in an academic context. We examine whether this assumption is ethically sound. Beyond providing the most up-to-date discussion of modafinil use in an academic context, this contribution includes an overview of the safety of modafinil use in greater depth than previous studies addressing the issue of cheating. Secondly, we emphasize two crucial, but hitherto nearly overlooked, nuances to the issues: (a) the potential for modafinil to decrease inequality and disadvantage in academic settings, and (b) the fact that how modafinil is used dramatically impacts its effects on health, coercion, fairness, authenticity and effort. Finally, we explicitly defend the position that there are no qualitatively morally relevant differences between modafinil use and other enhancement modalities; any such differences are in degree, not kind.